Health and Social Needs of Young Mothers. Issue 3 (May 2018) - Dumas, S. Amanda; Terrell, Ivy W.; Gustafson, Maggie
Abstract: Purpose: Teen parenting rates are disproportionately high among minority youth in the Southern United States. We explored barriers and unmet needs relating to medical and social support as perceived by these teen mothers, and elicited suggestions for improving their healthcare through the medical home. Study Design and Methods: We conducted four focus groups of 18- to 24-year-old mothers in New Orleans with questions designed to prompt discussions on young motherhood and healthcare. All 18 participants identified as African American, became mothers when <20, and their children were <5 at the time of the study. Two researchers independently analyzed focus group transcripts and coded them thematically, revealing various unmet social and health needs. Results: Seven main themes emerged, which revealed a concerning lack of mental healthcare, few with consistent medical homes, inadequate contraceptive knowledge and access, and a desire for parenting education and support groups. Suggestions for improving care largely centered around logistical and material support, such as extended clinic hours, transportation, and baby supplies. Clinical Implications: Findings suggest a need for improved medical knowledge, healthcare access, and social support for teen mothers. This may be provided through a multidisciplinary medical home model, such as a Teen-Tot clinic, where the unique challenges of adolescent parenting are continuously considered. Abstract : Adolescent mothers face many challenges. In this study, using focus group methodology, teen mothers were asked about their pregnancy and postpartum with a focus on various situations they faced and their suggestions for healthcare providers on how to improve their care.